Paleoenvironment of the Dalichai Formation, northeastern Semnan - Fereshteh Sajjadi; Firoozeh Hashemi Yazdi; Navid Navidi Izad; Fereshteh Sajjadi; Afsaneh Dehbozorgi (Journal of Stratigraphy and Sedimentology Researches, 2015)
Abstract Palaeonvironment of the Dalichai Formation, northeastern Semnan, is envisaged based on 69 samples studied palynologically. Diverse and well-preserved palynofloras, viz., miospores, dinoflagellate cysts, foraminiferal test linings, acritarchs, wood debris (plant tissue) and Amorphous Organic Matters (AOM) occur in the material examined. The presence of relatively abundant proximate dinoflagellates and Â±laevigate acritarchs in the lower part of the section studied implies sedimentation in a turbulent shallow environment. However, occurrence in the upper part of the section of abundant chorate dinoflagellates as well as notable proportion of blade-shaped to equal dimensional opaque palynomacerals seem to signify marine incursion and accumulation in an open marine setting. In most of the samples examined, prevalence of transparent AOM denotes a low oxygenated environment and slow rate of accumulation. Moreover, incidence of three palynofacies types (II, IV, VI) in the pertinent material also corroborates a shallow low oxygenated environment with low sedimentation rate which gradually deepened upward in the section.